Marine Coastal Spaces of Indigenous Peoples and Salmon Farming in Chile. Dilemmas in Historical Perspective [Espacios Costeros Marinos de Los Pueblos Originarios y Salmonicultura en Chile. Dilemas en Perspectiva Histórica*] - Carrasco-Bahamondes, D (Universidad de Concepcion, 2022)
The creation of the Marine Coastal Areas of Indigenous Peoples in Chile represents an important step forward in terms of indigenous policy. It implies the recognition of indigenous people as historical inhabitants of the edge of the sea and grants them the right to administer coastal areas to safeguard their customary uses. However, the implementation of this regulation has not been free of controversies, with requests being concentrated in geographic areas with a strong presence of aquaculture and salmon farming activities. The objective of this paper is to analyze the challenges and opportunities that Law 20.249 poses for the development and governance of Chiloé through a thematic review of studies and academic literature. Providing a temporal evolution perspective, the analysis allows identifying a reordering of forces between actors in the territory and opportunities for biodiversity conservation. The results identify the potential of these spaces to broaden the debate on the dynamics of territorial development and environmental governance in southern Chile. © 2022, Universidad de Concepcion. All rights reserved.